Full Order Model of Doubly-fed Wind Generator and Simplified Methods - Zhiyan Li; Qihui Liu; Xiaoming Wang (Institute of Advanced Engineering and Science, 2014)
Based on the control principle of the doubly-fed inductor wind power generator (DFIG for short), this article establishes the full order model, including the converter control model and the control sysem of balde angle, the correctness of the model is verified by hybrid real-time simulation and the electromagnetic numerical simulation, and the model realizes whole operation running characteristic control. In addition, this article puts forward simplified methods of DFIG model innovatively and establishes two different degrees of simplification models with equivalence of the converter model and the generator model respectively. The results by comparing the operating performance of each model under the same operating condition, show that, the two simplified models have high accuracy, and speed up the simulation efficiency effectively, which is suitable for the study of large-scale wind power generation in power system. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4518